IMPLEMENTASI PROGRAM PENANGGULANGAN KEMISKINAN TERPADU OLEH PAKEM PONTIANAK TIMUR - Budi Kurniawan E.01106093 (FISIP Universitas Tanjungpura, 2013)
Integrated Poverty Reduction Program between the public through public institutions of private and government institutions both atvillage and town level city. One of the government's policies and strategies in tackling povertyPontianak city is to run a PAKET Program through a partnership between the public and theprivate sector, giving rise to the city government coherence in these three elements in povertyalleviation through community empowerment. presence of several problems in the implementationof the Urban Poverty Program implementation especially in villages which are still less activeSaigon for example in the preparation of budget proposals PAKET late because no one elementpresence PAKET organizations themselves, as well as the disbursement schedule is notappropriate use of funding mechanisms so that program can not function properly.Key Words: Integrated Poverty Reduction Program, PAKEM organitations, ImplementationProcedures.